SISTEM INFORMASI PENGOLAHAN DATA NILAI SISWA: (Studi Kasus: SMK Taruna Bangsa Ciamis) - Abdurrahman Abdurrahman; Siti Solihah (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2021)
SMK Taruna Bangsa is a private school that has several departments, namely: NetworkCommunication Engineering, Light Vehicle Engineering, Motorcycle Engineering, Nursing,Pharmacy, and Office Automation and Governance. Web-based Student Value DataProcessing Information System is a system that provides information on student activenessreports online in the form of report values and information related to the student based on theweb, thus helping speed and quality in delivering information.The problem of this study is that there is often a delay in informing students of grades, thedelay in knowing the increase in students in each year, and the difficulty of printing examcards quickly. Therefore, in order to be able to answer the objectives of the study, it isnecessary to apply the PIECES analysis method. And the purpose of this study is toaccelerate in informing about academic differences between students, teachers, and parentsof students.Information system processing student value data, is an academic service intended forstudents, teachers and parents of students at Taruna Bangsa Vocational School in accessinginformation relating to academic records during the learning process. Teacher and studentinformation delivered includes student data information, teacher data information, valuedata, attendance, and exam card printing. even.Keywords: information systems, value processing, web